A complementariedade entre os princípios originais que distinguem os juízos analíticos e sintéticos elencados por Kant - Bergamasco, Alexsandro de Souza (2023)
This thesis examines the possibility of complementarity between the principles of distinction between analytical and synthetic judgments in Introduction B of the second edition of Kant's The Critique of Pure Reason. The Kantian theory describes that human knowledge is discursive. This means that there is noticing and classifying characteristic notes of objects conceptually in a judgment. Judgments, as to their justification, can be a priori or a posteriori. A priori judgments can be classified as analytical or synthetic. Kant lists four principles of distinction between analytical and synthetic judgments: Conceptual inclusion, non-contradiction, identity and conceptual elucidation. The distinction has encountered controversies since the release of the second edition of the Critique of Pure Reason, and it has been accompanied by many subsequent debates about which criterion would be the most fundamental. The thesis argues that Kant's four principles for distinguishing between analytic and synthetic judgments complement each other in order to allow a return to the originality of the distinction as elaborated by Kant himself.